Group counseling as self-management intervention for former mental health patients: A case study - Abu Yazid Abu Bakar; Nurul Anis Azizi; Siti Khadijah Hashim (Indonesian Institute for Counseling, Education and Theraphy, 2020)
The aim of the study conducted in order to help and to give exposure for the group members on how to build self-confidence in facing society. Three objectives of the study are 1) to build self- confidence among group members on how to face society, 2) to encourage and to give support in self-motivation towards well-being among group members and 3) to give awareness for the group members that this life needs courage and positive thoughts which are more meaningful. The method of this study was conducted a group counselling session involving six mental health patients who are recovered and still under doctor observation at the Hospital Canselor Tuanku Mukhriz (HCTM), which is under the Day Care Community Psychiatry, Medical Centre and Faculty of Medicine, Universiti Kebangsaan Malaysia (UKM). The findings show that the responsiveness of respondents’ self-management is still lacking as they are still in the process of recovering and monitoring from Psychiatrists and Counsellor Officers at HCTM for time to time.